Variability in quality attributes of paprika and paprika alike chillies (Capsicum annuum L.) - T J Zachariah, N K Leela, K N Shiva, P Gobinath, (Journal of Spices and Aromatic Crops, 2014)
An investigation was carried out to assess the variability in paprika alike chillies (26 indigenous germplasm) and paprika lines (18 exotic collections) for yield and quality attributing parameters, which would inturn help in identifying and utilizing the promising lines for crop improvement. Highly significant variation was recorded among the genotypes for yield and quality contributing characters. Kt-Pl-19, Kt-Pl-19 variant–I, ICBD-10, ICBD-8, SSP-1999 and PBC-171, were found promising, while ICBD-10, ICBD-8, ICBD-1, ICBD-11, ICBD-6, ICBD-19, CC-1, EC-171, EC-490, EC-18, EC-6, EC-45, EC-71 and EC-14 proved to be ideal for quality attributes. Based on yield and quality parameters, the genotypes ICBD-10, ICBD-8 and EC-18 were found suitable for paprika industry with high yield (> 850 g plant–1) and high quality attributing characters (> 200 ASTA units and < 0.5% capsaicin). Among the various characters, maximum coefficient of variation (15.25%) was recorded for capsaicin content in both indigenous and exotic germplasm and minimum variation for color value (0.46%) in the indigenous germplasm and weight of pericarp (6.78%) in the exotic collections.